Analisis Manajemen Kontrol Bank Syariah Indonesia Dalam Penanganan Permasalahan Pengguna Automatic Teller Machine (ATM) - Muhammad Latiful Fatih; Nurbaiti Nurbaiti; Nikmah Dalimunthe (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This research uses qualitative research methods, this research is also called artistic research because this research is less patterned or more varied in nature. Interpretation of data collected in the field during research is the main focus of this research. With a case study approach, this research is a type of qualitative research. This research results that the application of control management is a function to supervise every activity that has been organized, control management is the last part of the management function where the control management function of the Automatic Teller Machine becomes the material for supervising activities on the machine which is then the result of the application of control management This will be reported and used as material for evaluating a company. Problems that commonly occur in transactions at Automatic Teller Machines include failure to withdraw cash, and ATM cards being swallowed, which are problems beyond the control of Bank Syariah Indonesia KCP Stabat KH Zainal Arifin